The Influence of Digital Textbooks on Narrative Writing Skills of Primary School Teacher Education Students - Wijayanti, Atrianing Yessi; Zulaeha, Ida; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Journal of language teaching and research, 2025)
In this digital era, technological advancements have transformed many aspects of education, including the way learning materials are delivered. One of the innovations emerging from technological progress is digital textbooks, which offer ease of access and interactivity in learning. In the context of language learning, digital textbooks hold great potential for supporting the development of writing skills, including narrative writing. This research aims to determine whether digital textbooks have an impact on the narrative writing skills of Primary School Teacher Education students. This study employs a quantitative research approach, using an experimental method. The population in this study consists of 57 students from the Faculty of Teacher Training and Education, specifically from the Primary School Teacher Education program, comprising 30 students from semester III A and 27 students from semester III B. The sampling technique used in this study is a type of nonprobability sampling, specifically saturated sampling. Data collection in this research is conducted through testing. The validity test in this study uses content validity. The results of the hypothesis testing, conducted through an Independent Samples t-Test, show a significance value of 0.001 < 0.05 and a calculated t-value of 3.472 > t-table value of 2.0024. This means that Ho is rejected and Ha is accepted, thus it can be concluded that there is an influence of digital textbooks on the narrative writing skills of Primary School Teacher Education students.